PELAKSANAAN KURIKULUM 2013 PADA PEMBELAJARAN GEOGRAFIDI SMA NEGERI 2 BANJARMASIN - Irfan Prasetyady Noor (JURNAL SOCIUS, 2017)
In curriculum 2013 subjects geography grouped in a subjects the social science so the assessment more directed at the point of view of the existence and human activity influenced by dynamics of the physical. This study aims to obtain objective information about the implementation of curriculum 2013. This study adopted an method to inductive qualitative to explore qualitatively every finding in the field. Key person (community leaders and government officers) as source of invaluable information was selected purposive sampling. Ap proaches such as indepth interviews and observation, provide useful tools in primary data collection. Secondary data are mainly collected by literature study and documents study.Based on the results of the study found that the obstacles experienced by the school has two aspects, (a) communication less intensive, causing lack of understanding of the curriculum 2013 material in their entirety among in schools; (b) weak supervision and monitoring aspects, causing the schools do not know in which a part in the document of curriculum 2013 and implementation still need to improved with the provisions. Factors that affects the implementation of the curriculum 2013 at the school, covering four factors: (a) communication, (b) human resources, (c) the policy, and (d) environment in order to improve the quality of human resources in the implementation of the program curriculum of 2013, it needs to be emphasized the importance of efforts to improve the quality, frequency, and equitable education and training activities, workshops, and other similar activities.Keywords: Curriculum 2013, learning, and geography Kurikulum 2013 mata pelajaran geografi dikelompokkan pada rumpun Mata Pelajaran Peminatan Ilmu-ilmu Sosial sehingga kajiannya lebih diarahkan pada sudut pandang keberadaan dan aktivitas manusia yang dipengaruhi oleh dinamika alam fisik.Penelitian ini bertujuan untuk memperoleh informasi objektif mengenai pelaksanaan Kurikulum 2013. Penelitian ini menggunakan metode induktif kualitatif. Metode ini memungkinkan peneliti mengeksplorasi setiap temuan di lapangan, yang dijelaskan secara deskriptif kualitatif. Tokoh kunci dipilih menggunakan purposive sampling yaitu menentukan objek/subjek sesuai tujuan. Berbagai pendekatan seperti wawancara mendalam dan observasi, menjadi alat yang penting dalam pengumpulan data primer. Pangumpulan data sekunder dilakukan melalui studi pustaka dan studi dokumen.Berdasarkan hasil penelitian ditemukan bahwa Tahap persiapan yaitu perencanaan pembelajaran yang diwujudkan dengan kegiatan penyusunan rencana pelaksanaan pembelajaran (RPP) geografi. Tahap pelaksanaan pembelajaran geografi merupakan implementasi dari RPP dan kegiatannya meliputi tahap pendahuluan, inti dan penutup. Faktor-faktor yang mempengaruhi pelaksanaan Kurikulum 2013 disekolah, yaitu meliputi empat faktor: (a) komunikasi, (b) sumber daya manusia, (c) isi kebijakan , dan (d) lingkungan.Dalam rangka meningkatkan kualitas sumberdaya manusia dalam pelaksanaan program Kurikulum 2013, maka perlu ditekankan pentingnya upaya peningkatan kualitas, frekuensi, dan pemerataan kegiatan pendidikan dan pelatihan, workshop, dan kegiatan lain yang sejenis.Kata Kunci: Kurikulum 2013, pembelajaran, dan geografi